Public risk perceptions, emotions and behaviours under a major epidemic: A structural equation model analysis - Wang, Dandan; Zhang, Aihua; Feng, Xianqiong (Journal of advanced nursing, 2023)
Aim To explore the relationships between public risk perceptions, emotions and behaviours during a major epidemic. Design Exploratory cross‐sectional design. Methods The 701 subjects were surveyed using self‐administered questionnaires, including the General Information Questionnaire, Public Risk Perceptions Questionnaire, Public Emotions Questionnaire and Public Behaviours Questionnaire. The results were analysed using structural equation modelling, and mediated effects were probed at the same time. Results The median of the total scores of the Public Risk Perceptions Questionnaire was 70, the median of the total scores of the Public Emotions Questionnaire was 65 and the median of the total scores of the Public Behaviours Questionnaire was 83. Spearman's correlation analysis showed that the correlation coefficient ρ between public risk perceptions and emotions was 0.26 (p < 0.01); the correlation coefficient ρ between risk perceptions and behaviours was 0.36 (p < 0.01); and the correlation coefficient ρ between emotions and behaviours was 0.37 (p < 0.01). After many rounds of correction, the final model was established, the fit was good, and the results of the mediating effect analysis showed that the level of public risk perceptions under a major epidemic had a direct positive effect on public emotions (β = 0.41, p < 0.01) and public behaviours (β = 0.51, p < 0.01). The level of public risk perceptions also had an indirect positive effect on behaviours by affecting public emotions (β = 0.11), while public emotions had a direct positive effect on public behaviours (β = 0.27, p < 0.01). Conclusions Our findings revealed that public perceptions and public emotions directly influenced public behaviours. Additionally, public perceptions can indirectly influence public behaviours through public emotions.